Rotational Dynamics of Optically Trapped Human Spermatozoa - Elavarasan Subramani; Himanish Basu; Shyam Thangaraju; Sucheta Dandekar; Deepak Mathur; Koel Chaudhury (The Scientific World Journal)
Introduction. Optical trapping is a laser-based method for probing the physiological and mechanical properties of cells in a noninvasive manner. As sperm motility is an important criterion for assessing the male fertility potential, this technique is used to study sperm cell motility behavior and rotational dynamics. Methods and Patients. An integrated optical system with near-infrared laser beam has been used to analyze rotational dynamics of live sperm cells from oligozoospermic and asthenozoospermic cases and compared with controls. Results. The linear, translational motion of the sperm is converted into rotational motion on being optically trapped, without causing any adverse effect on spermatozoa. The rotational speed of sperm cells from infertile men is observed to be significantly less as compared to controls. Conclusions. Distinguishing normal and abnormal sperm cells on the basis of beat frequency above 5.6 Hz may be an important step in modern reproductive biology to sort and select good quality spermatozoa. The application of laser-assisted technique in biology has the potential to be a valuable tool for assessment of sperm fertilization capacity for improving assisted reproductive technology.